2023
DOI: 10.1021/acs.jcim.3c00465
|View full text |Cite
|
Sign up to set email alerts
|

MolSHAP: Interpreting Quantitative Structure–Activity Relationships Using Shapley Values of R-Groups

Abstract: Optimizing the activities and properties of lead compounds is an essential step in the drug discovery process. Despite recent advances in machine learning-aided drug discovery, most of the existing methods focus on making predictions for the desired objectives directly while ignoring the explanations for predictions. Although several techniques can provide interpretations for machine learning-based methods such as feature attribution, there are still gaps between these interpretations and the principles common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Interpretation approaches can be classified into two categories: global and local, corresponding to focusing on the prediction model itself and input instances, respectively. Various studies were reported on the local interpretation methods and associated applications, such as the identification of important substructures (atoms) in a molecule, compound optimization , and finding a potential artifact of a model . On the other hand, methods for global interpretations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation approaches can be classified into two categories: global and local, corresponding to focusing on the prediction model itself and input instances, respectively. Various studies were reported on the local interpretation methods and associated applications, such as the identification of important substructures (atoms) in a molecule, compound optimization , and finding a potential artifact of a model . On the other hand, methods for global interpretations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…( b ) virtual screening and drug design . Some methods, algorithms, and functional tools were constructed to facilitate the application or improve the performance of the classic virtual screening strategy. Machine learning methods were also adopted in this collection to identify new hit compounds, discover promising leads for cholestasis, interpret QSAR models, and learn molecular representations. DiStefano et al and Mao et al conducted research on toxicity prediction and antiviral drug design, respectively. Moreover, ML was also applied to explore the pharmaceutical properties of diverse drug candidates. A novel knowledge base for nonalcoholic fatty liver disease was developed .…”
mentioning
confidence: 99%
“…Recently, Shapley values have been expansively adopted in the realm of machine learning, especially in elucidating model decisions. Within the ambit of substructure importance analysis, conventional methodologies often perceive substructures as autonomous entities, determining their relevance based on model predictions.…”
mentioning
confidence: 99%